Analisis Ekonomi Penggantian Pakan Komersial dengan Ampas Kecap Ekstrusi dan Ampas Kecap Fermentasi pada Pemeliharaan Ayam Pedaging - Damaryanto Widharto; Lusia Risyani P. M. (AGRIMOR, 2020)
The research was conducted to know influence of extruded and fermented soybean pulp in commercial feed on feed conversion, feed cost per gain and income over feed cost. The research use 60 day old chick of broilers which were devided into 4 treatments, that is 1) were given commercial feed without substitution of extruded and fermented soybean pulp (T-0), 2) were given commercial feed with substitution of extruded soybean pulp as much as 5% (T-1), and 3) were given commercial feed with substitution of fermented soybean pulp as much as 5% (T-2). The variables observed is feed conversion, feed cost per gain, and income over feed cost. The result showed that given commercial feed with substitution of extruded and fermented soybean pulp can decrease of feed conversion and feed cost per gain but increase of income over feed cost. Feed conversion is 2.51 (T-0), 2.27 (T-1), and 2.32 (T-2), feed cost per gain Rp. 20.080,- (T-0), Rp. 17.473,33,- (T-1) and Rp. 17.878,50,-/kg (T-2), and Income over feed cost Rp. 4.223,20,- (T-0), Rp. 6.897,85,- (T-1) and Rp. 7.223,15,-/kg (T-2). Research conclusion is substitution of extruded and fermented soybean pulp in commercial feed can decrease of feed conversion and feed cost per gain but increase of income over feed cost.